2017
DOI: 10.1088/1748-9326/aa7030
|View full text |Cite
|
Sign up to set email alerts
|

A national assessment of underground natural gas storage: identifying wells with designs likely vulnerable to a single-point-of-failure

Abstract: The leak of processed natural gas (PNG) from October 2015 to February 2016 from the Aliso Canyon storage facility, near Los Angeles, California, was the largest single accidental release of greenhouse gases in US history. The Interagency Task Force on Natural Gas Storage Safety and California regulators recently recommended operators phase out single-point-of-failure (SPF) well designs. Here, we develop a national dataset of UGS well activity in the continental US to assess regulatory data availability and unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Michanowicz et al. () documented a total of 14,138 injection and withdrawal wells in the United States (as of 2016) having a wide range of ages and years of operation, although more than 17,000 wells have been suggested (Folga et al., ; Joint Industry Task Force, ). Moreover, the total number of occurrences includes those having a wide range of severities and consequences, from minor nuisance occurrences through catastrophic occurrences (such as some of those noted in the IFR).…”
Section: Occurrence Frequencies As Arithmetic Meansmentioning
confidence: 99%
See 1 more Smart Citation
“…Michanowicz et al. () documented a total of 14,138 injection and withdrawal wells in the United States (as of 2016) having a wide range of ages and years of operation, although more than 17,000 wells have been suggested (Folga et al., ; Joint Industry Task Force, ). Moreover, the total number of occurrences includes those having a wide range of severities and consequences, from minor nuisance occurrences through catastrophic occurrences (such as some of those noted in the IFR).…”
Section: Occurrence Frequencies As Arithmetic Meansmentioning
confidence: 99%
“…Porous‐rock storage thus represents some 91% of UGS facilities in the United States, with solution‐mined salt caverns comprising the remainder. Approximately 14,138 injection and withdrawal wells service UGS facilities in the United States, with 88% in depleted oil‐and‐gas fields, 11% in aquifers, and 1% in salt caverns (Michanowicz et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…During the Aliso Canyon blowout, estimated emission rates from AVIRIS-C were consistent with those obtained by Scientific Aviation. Michanowicz et al (2017) identified 160 UGS facilities that use wells that were not designed for gas storage, like the well that failed at Aliso Canyon, suggesting the possibility for future blowouts. Airborne imaging of methane plumes offers the potential to quantify methane emissions while locating primary and secondary emission sources, as demonstrated in this study for Aliso Canyon.…”
Section: Resultsmentioning
confidence: 99%
“…We used previously published data on UGS facilities and wells from Michanowicz [26]. Well counts included all active wells connected to active UGS facilities from the April 2016 Energy Information Administration-191 M Monthly Underground Gas Storage Report [31].…”
Section: Methodsmentioning
confidence: 99%
“…First, UGS wells are geographically dispersed across 32 U.S. states. Recent obsolescence issues identified at UGS facilities (e.g., single-point-of-failure well designs) have placed new scrutiny on the hazards they may pose to nearby populations [26–28]. Second, the Interagency Task Force on Natural Gas Storage Safety, which was formed after the 2015 Aliso Canyon leak, recommended that “stakeholders should collect and analyze data on the proximity of UGS facilities to population centers to help better quantify some of the risk factors” [27].…”
Section: Introductionmentioning
confidence: 99%